THE MECHANISM FOR UTILIZING TOBACCO PRODUCT EXCISE REVENUE SHARING FUNDS (DBH-CHT) IN BOJONEGORO REGENCY IS REVIEWED BASED ON THE THEORY OF DIGNITY JUSTICE - Putri Freda Cayadewi; Gunawan Hadi Purwanto; Asri Elies Alamanda (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
The Tobacco Product Excise Revenue Sharing Fund (DBH-CHT) is a fiscal instrument allocated by the central government to tobacco-producing regions and/or the tobacco product industry as a form of fiscal equity and support for community welfare. Bojonegoro Regency as one of the tobacco-producing areas obtained a significant allocation of DBH-CHT and used it for the fields of community welfare, health, and law enforcement. However, in practice, the mechanism for utilizing DBH-CHT still faces challenges related to target accuracy, inter-agency coordination, and program effectiveness. This study aims to analyze the mechanism of utilization of DBH-CHT in Bojonegoro Regency and assess it based on the Theory of Dignity Justice. The research method used is normative-empirical legal research with a legislative and conceptual approach. Data was obtained through literature studies on laws and regulations and interviews with relevant agencies within the Bojonegoro Regency Government and the Customs and Excise Office. The results of the study show that the management of DBH-CHT in Bojonegoro Regency in general has been carried out in accordance with the provisions of laws and regulations, especially the Minister of Finance Regulation Number 72 of 2024 and Regent Regulation Number 24 of 2011. The use of DBH-CHT is directed at programs that have a direct impact on tobacco farmers, farm workers, cigarette factory workers, and vulnerable communities through social assistance, skill development, health insurance, and law enforcement in the excise sector. Judging from the Theory of Dignity Justice, the mechanism for utilizing DBH-CHT in Bojonegoro Regency not only fulfills procedural justice, but also reflects substantive justice by placing human welfare and dignity as the main goal of public policy.